The development of a guideline implementability tool (GUIDE-IT): a qualitative study of family physician perspectives - Kastner, Monika; Estey, Elizabeth; Hayden, Leigh; Chatterjee, Ananda; Grudniewicz, Agnes; Graham, Ian D; Bhattacharyya, Onil (Université d'Ottawa | University of Ottawa, 2014)
Abstract Background The potential of clinical practice guidelines has not been realized due to inconsistent adoption in clinical practice. Optimising intrinsic characteristics of guidelines (e.g., its wording and format) that are associated with uptake (as perceived by their end users) may have potential. Using findings from a realist review on guideline uptake and consultation with experts in guideline development, we designed a conceptual version of a future tool called Guideline Implementability Tool (GUIDE-IT). The tool will aim to involve family physicians in the guideline development process by providing a process to assess draft guideline recommendations. This feedback will then be given back to developers to consider when finalizing the recommendations. As guideline characteristics are best assessed by end-users, the objectives of the current study were to explore how family physicians perceive guideline implementability, and to determine what components should comprise the final GUIDE-IT prototype. Methods We conducted a qualitative study with family physicians inToronto, Ontario. Two experienced investigators conducted one-hour interviews with family physicians using a semi-structured interview guide to 1) elicit feedback on perceptions on guideline implementability; 2) to generate a discussion in response to three draft recommendations; and 3) to provide feedback on the conceptual GUIDE-IT. Sessions were audio taped and transcribed verbatim. Data collection and analysis were guided by content analyses. Results 20 family physicians participated. They perceived guideline uptake according to facilitators and barriers across 6 categories of guideline implementability (format, content, language, usability, development, and the practice environment). Participants’ feedback on 3 draft guideline recommendations were grouped according to guideline perception, cognition, and agreement. When asked to comment on GUIDE-IT, most respondents believed that the tool would be useful, but urged to involve “regular” or community family physicians in the process, and suggested that an online system would be the most efficient way to deliver it. Conclusions Our study identified facilitators and barriers of guideline implementability from the perspective of community and academic family physicians that will be used to build our GUIDE-IT prototype. Our findings build on current knowledge by showing that family physicians perceive guideline uptake mostly according to factors that are in the control of guideline developers.